Comparative study on dermatoglyphics in patients with PTSD - Glamuzina, Ljubomir; Mihanović, Mate, liječnik; Miličić, Jasna; Devčić, Sanja, liječnica; Restek-Petrović, Branka (2009)
Abstract: The factors situated at the bases of the genesis and development of PTSD are divided in: biological, psychological and social factors. Primary factor is a stressful event of extremely dangerous and threatening nature. The sort and the intensity of the stressful event too play an important role, followed by the personality structure, the relation with the environment and the genetic constitution. The study was thought to determine the quantitative dermatoglyphic properties of the digito-palmar complex in patients with PTSD aiming to establish whether there are biological, that is, genetic bases for PTSD, in what measure they determine the clinical manifestation of the disorder, and whether there is a dermatoglyphic marker, characteristic for people with PTSD.
We analyzed the quantitative properties of the digito-palmer complex on a group of 100 male examinees over 18 years of age with PTSD, no psychiatric comorbidity, and who were two or more times cured at the Psychiatric Hospital »Sveti Ivan«, comparing them with the quantitative dermatoglyphic properties of a group of 100 phenotypically healthy male examinees over 18 years of age. Using the method of descriptive statistics, we found no statistically significant differences among the results of the examined groups. With the T-test we evaluated the heterogeneity of the groups, and the results showed the existence of statistically significant differences among the comparison group and the group of patients with PTSD on three variables. We calculated the Fluctuating Asymmetry (FA) measure, which illustrates the compatibility, that is, the symmetry of the observed property on the right and on the left side of the body, indicating a difference on one variable.
The outcome did not confirm the existence of a connection between a particular dermatoglyphic result and the genesis of PTSD. This is, however, in line with the hypothesis that, in patients with PTSD and other psychiatric disorders, there is a multiple effect of several micro-abnormalities in different genes, along with the inevitable and essential influence of environmental and/or physical and/or psychosocial stressogenic factors
Bibliografija: 43 jed
Sažetak
Keywords: Dermatoglifi -- Digitopalmarni kompleks -- Posttraumatski stresni poremećaj